Language of the underground: Openly-covert communication around commercial sex in Malang nightlife community - Zaki, Ibnuz (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
As something generally considered private, sex and its surrounding activities are something rarely discussed, especially in a country like Indonesia where such is just taboo. This study undertakes the exact opposite of that, discussing how male “sex buyers” share their prostitution-related stories to their online community called Malang Nightlife. This study concerns how language is used by a certain community in their collective repertoire(s) as a representation of a proactive action showing a liking or support for prostitution. Accordingly, lexico-semantic analysis is the primary treatment given to the data, complemented with views on multilingualism and sociopragmatics to contextualise these intrinsic linguistic features in their naturally social settings. The findings suggest that 1) the community has quite strict rules regarding how members are allowed—and not—to share their story; 2) they often use four-way multilingualism in telling their stories (i.e. Indonesian, Javanese, English, and Basa Walikan Malang); 3) the members have several common tendencies and conventions in telling their stories; 4) these stories seem to be constructed from personal or collective repertoires each member has access to or have familiarity with. The conclusion drawable from this study is closely related to public’s stereotypes towards males and their sexual wrong-doings, up to the point of objectifications by these said males to the female prostitutes they refer to in their stories.